2023
DOI: 10.24018/ejvetmed.2023.3.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Curative Effects of Spirulina (Spirulina platensis) Aqueous Extract on Reproductive Parameters and Oxidative Stress Markers in Female Guinea Pig (Cavia porcellus) Exposed to Lead

Abstract: Some medicinal plants with antioxidant properties have protective effects on reproductive parameters and neutralize the harmful effects of hazardous. Spirulina possesses high concentration of nutrients responsible of their biological activities and nutritional properties. The present study aimed at assessing the protective effect of aqueous extract of Spirulina platensis (AESP) in alleviating the lead-induced impairment of reproductive function in female guinea pig. For this purpose, Sixty (60) sexually mature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This effect is attributed to SP because it has effects that work on the production of testo, which is the main androgen in the testicle, in Leydig cells, which directly depends on the stimulation of testicular hormone (LH), which stimulates muscle growth and sexual activity [19]. The results of the study didn't agree with [20,21,22] who showed that spirulina did not significantly affect the level of interstitial cell-stimulating hormones (LH and FSH) in laboratory animals, pigs, and goats for a period of 60 days.…”
Section: Effect Of Adding Protein and Spirulina Algae On Hormones In ...mentioning
confidence: 91%
“…This effect is attributed to SP because it has effects that work on the production of testo, which is the main androgen in the testicle, in Leydig cells, which directly depends on the stimulation of testicular hormone (LH), which stimulates muscle growth and sexual activity [19]. The results of the study didn't agree with [20,21,22] who showed that spirulina did not significantly affect the level of interstitial cell-stimulating hormones (LH and FSH) in laboratory animals, pigs, and goats for a period of 60 days.…”
Section: Effect Of Adding Protein and Spirulina Algae On Hormones In ...mentioning
confidence: 91%
“…A score of 0-3 indicates the severity of diarrhoea, which is examined using pig faeces. The mortality rate represents the proportion of pigs that die from the total number during the experimental period (Sorelle et al 2023). Equations 1 and 2 represent the mathematical expression of diarrhoea rate and mortality rate.…”
Section: Indicator Measurement Methodsmentioning
confidence: 99%